2018
DOI: 10.3390/antiox7100127
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Neutrophil Dynamics and Function in Exercise-Induced Muscle Damage and Delayed-Onset Muscle Soreness: Effect of Hydrogen Bath

Abstract: The purpose of this study was to investigate the involvement of neutrophil dynamics and function in exercise-induced muscle damage (EIMD) and delayed-onset muscle soreness (DOMS), and the effect of molecular hydrogen (H2) intake on these parameters. Nine healthy and active young men performed H2 and placebo bath trial in a crossover design. They carried out downhill running (−8% slope) for 30 min at a speed corresponding to 75~85% of peak oxygen uptake (VO2peak). Subsequently, they repeated bathing for 20 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…As described above, there is no conclusive evidence regarding the effectiveness of H 2 bathing against muscle damage, secondary oxidative stress, and inflammation after eccentric exercise [21,22]. Moreover, although the associated mechanism of action has not been elucidated, our results have shown that H 2 may alleviate DOMS after eccentric exercise [21].…”
Section: H 2 Bathingmentioning
confidence: 55%
See 1 more Smart Citation
“…As described above, there is no conclusive evidence regarding the effectiveness of H 2 bathing against muscle damage, secondary oxidative stress, and inflammation after eccentric exercise [21,22]. Moreover, although the associated mechanism of action has not been elucidated, our results have shown that H 2 may alleviate DOMS after eccentric exercise [21].…”
Section: H 2 Bathingmentioning
confidence: 55%
“…Although the effectiveness of oral intake of H 2 water [18,19] and H 2 bathing [21,22] has not been demonstrated, intravenous infusion of H 2 -saline [23] and inhalation of H 2 gas [24] have been reported to suppress exercise-induced oxidative stress and/or inflammation. However, the antioxidant and anti-inflammatory effects of H 2 intake have been observed only in animals [23,24], and these effects have not been confirmed in humans regardless of the administration route [18,19,21,22]. Regarding the timing of H 2 administration, it seems to be most effective before [23] or simultaneously with exercise [24].…”
Section: Summary Of the Results Of Previous Studiesmentioning
confidence: 99%
“…Prolonged strenuous exercise may induce unfavorable biological changes and symptoms, including inflammatory responses, such as leukocyte infiltration [1][2][3]; gastrointestinal (GI) incidents, such as diarrhea, nausea, and gastric pain [4][5][6]; delayed-onset muscle soreness; muscle and internal organ injury; and immune suppression [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exhaustive exercise might cause mechanical injury of muscles and activates macrophages, which results in increased synthesis and secretion of proinflammatory cytokines, such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). These cytokines also stimulate macrophages to secrete prostaglandins causing muscle soreness, and lead to exercise-induced fatigue (Pawlik et al, 2016;Kawamura et al, 2018;Yang et al, 2019). In addition, the hippocampus is an important brain region that is vulnerable to stress and is involved in the exercise-induced fatigue (Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%